The effect of foot bath on sleep quality in the elderly: a systematic review - Khadijeh Nasiri; Mohammad Shriniy; Nazila Javadi Pashaki; Vahideh Aghamohammadi; Solmaz Saeidi; Maryam Mirzaee; Mostafa Soodmand; Esmail Najafi (BMC Geriatrics, 2024)
Abstract Introduction Population aging is a problem that has affected most countries in the world. Poor-quality sleep is a common complaint among the elderly. Foot baths are a method of heat therapy and are performed as an independent nursing care in different departments. The present study was conducted with the aim of investigating the effects of foot baths with spa on improving the sleep quality of the elderly. Methods This research is a systematic review. We systematically searched six databases, including Google Scholar, PubMed, Web of Science, Scopus, Embase, and the World Health Organization databases, to retrieve the related articles based on the keywords used in our search strategy from 2010 to March 2023. Result Finally, 10 articles were included in this study. All studies were randomized controlled trial (RCTs) and semi-experimental. In all 9 studies, the positive effects of the foot bath were reported. In 9 studies, the effect of foot baths with water above 40 degrees Celsius was reported. The PSQR questionnaire was used in most of the studies. Conclusion The total findings of this study showed that due to the high prevalence of sleep problems in the elderly, foot baths with warm water can be used as an easy, simple, and safe nursing intervention to improve sleep quality. Therefore, it can be used in nursing homes and hospitals. It is also a non-pharmacological and inexpensive nursing intervention that can be implemented by the elderly themselves after training by community health nurses.